Work Accident Risk Assessment in Hot Rolled Coil Production with The Failure Mode, Effect and Criticality Analysis (FMECA) Method at PT XYZ - Adiyatma, Naufal Abiyyu; Sari, Mega Mutiara; Ridhosari, Betanti (Journal of Sustainable Infrastructure, 2024)
In HRC production at PT XYZ which is carried out continuously to pursue the production target will be in effect on the HRC production component with the risk management methods is Failure Mode, Effect and Criticality Analysis (FMECA). The purpose of this study is to identify the source of potential failure in HRC production, analyze the RPN value, and determine control recommendations. Data collection methods are carried out by means of direct observation of HRC production, interviews, and literature studies. The results on the risk assessment by the FMECA method are leakage and operational failure of the burner device with a RPN value of 420, the Refractory Brick Furnace crack of 324, the scale piece bounced off the 294 reservoir, the oil leak on the flat pass, the work roll, and the backup roll of 252 , damage to the roller table machine is 240, operational failure on the Looper engine of 240, and the failure of the HRC product binding manually is 240. Risk control in HRC production is the use of flame rod indicators, ultraviolet sensors, ultrasonic tests, installation of slab pieces cover, thermal infrared camera, LOTO use, quadratic linear inverse system or predictive control, distance guard, and periodic maintenance.